The judicial politics of "burqa bans" in Belgium and Spain: socio-legal field dynamics and the standardization of justificatory repertoires - Burchardt, Marian (Working papers, 2017)
Over the past decade, controversies over Islamic face veiling have become increas ingly widespread in societies across Europe. This article comparatively explores the socio-legal dynamics of claims-making by proponents and opponents of prohibit ing full-face coverings in Belgium and Spain. In Belgium, a federal ban of full-face coverings was adopted in July 2011 and, after intensive judicial struggles, received judicial validation by the Constitutional Court in 2012. In Spain, local burqa contro versies led to municipal bans in the region of Catalonia in 2010, which were annulled by the Supreme Court in 2013 after effective legal counter-mobilizations. Our key argument is that, the diverging legal outcomes notwithstanding, as burqa controver sies are transposed from locally embedded political fields to transnationally situated judicial fields the justificatory repertoires employed are increasingly standardized. It is this standardization of justificatory repertoires that, in the long run, has facili tated the rapid spread of ‘burqa bans’.